The Effect Of Advertising Messages, Ads Attraction and Celebrity Endorser on Purchase Decisions for Yamaha Mio Products (Case Study in West Jakarta Administrative City) - Surya Sumantri (Warta Pendidikan | e-Journal, 2021)
This study aims to analyze the influence of advertising messages, advertising attractiveness and celebrity endorser towards on purchase decision of Yamaha Mio. The primary data were derived from questionnaire and the secondary data were from company statistics. The population of the research comes from all citizens of west Jakarta Municipality who used Yamaha Mio. The method of analysis used in this study is multiple linear regression. The results show that advertising messages, advertising attractiveness and celebrity endorser together have a significant effect on purchasing decisions. Partially advertising message, advertising attractiveness and celebrity endorser have a significant positive effect on purchasing decision. The most advertising attractiveness is powerfull variable of influence on purchasing decisions.